Clinical spectrum and outcomes of crescentic glomerulonephritis: A single center experience - S K Rampelli (Indian Journal of Nephrology, 2016)
There is limited data on the etiology, clinical and histopathological spectrum and outcomes of crescentic glomerulonephritis (CrGN) in adult Indian population. This prospective study was done to evaluate the etiology, clinicohistological patterns and predictors of outcome of CrGN in South Indian population. All the patients received standard protocol based immunosuppression in addition to supportive care. Immune-complex glomerulonephritis (ICGN) was the most common etiology (n = 31; 77.5%) followed by pauci-immune glomerulonephritis (PauciGN; n = 8; 20%) and anti-glomerular basement membrane disease (n = 1; 2.5%). The most common etiology of ICGN was IgA nephropathy (n = 11; 27.5%) followed by lupus nephritis (n = 7; 17.5%) and post-infectious glomerulonephritis (PIGN) (n = 7; 17.5%). The patients with PauciGN were significantly older compared to those with ICGN (44.5 ± 15 years vs. 31.8 ± 11 years; P = 0.01). The patients with PauciGN presented with significantly higher serum creatinine (9.7 ± 4.4 vs. 6.6 ± 3.3 mg/dl; P = 0.03). The histopathologic parameters of ICGN and PauciGN were comparable except for a higher proportion of sclerosed glomeruli in ICGN. At the end of 3 months follow-up, only two patients went into complete remission (5.4%). Majority of the patients had end-stage renal failure (48.6%) and were dialysis dependent and seven patients (18.9%) expired. There was no signifi difference in the renal survival (10.9 ± 1.9 vs. 9.6 ± 3.3 months) or patient survival (17.5 ± 2.1 vs. 17.3 ± 4.3 months). The parameters associated with adverse outcomes at 3 months were hypertension (odds ratio [OR]: 0.58; confidence interval [CI]: 0.36–0.94), need for renal replacement therapy (OR: 0.19; CI: 0.04–0.9), serum creatinine at admission (P = 0.019), estimated glomerular filtration rate (P = 0.022) and percentage of fibrocellular crescents (P = 0.022).